Mixed tocopherols inhibit platelet aggregation in humans: potential mechanisms - Liu, Meilin; Wallmon, Agneta; Olsson-Mortlock, Caroline; Wallin, Rolf; Saldeen, Tom (The American journal of clinical nutrition, 2003)
Epidemiologic studies have shown an inverse correlation between acute coronary events and high intake of dietary vitamin E. Recent clinical studies, however, failed to show any beneficial effects of alpha-tocopherol on cardiovascular events. Absence of tocopherols other than alpha-tocopherol in the clinical studies may account for the conflicting results. This study compared the effect of a mixed tocopherol preparation rich in gamma-tocopherol with that of alpha-tocopherol on platelet aggregation in humans and addressed the potential mechanisms of the effect. Forty-six subjects were randomly divided into 3 groups: alpha-tocopherol, mixed tocopherols, and control. ADP and phorbol 12-myristate 13-acetate-induced platelet aggregation, nitric oxide (NO) release, activation of endothelial constitutive nitric-oxide synthase (ecNOS; EC 1.14.13.39) and of protein kinase C (PKC), and ecNOS, superoxide dismutase (SOD; EC 1.15.1.1), and PKC protein content in platelets were measured before and after 8 wk of administration of tocopherols. ADP-induced platelet aggregation decreased significantly in the mixed tocopherol group but not in the alpha-tocopherol and control groups. NO release, ecNOS activation, and SOD protein content in platelets increased in the tocopherol-treated groups. PKC activation in platelets was markedly decreased in the tocopherol-treated groups. Mixed tocopherols were more potent than alpha-tocopherol alone in modulating NO release and ecNOS activation but not SOD protein content or PKC activation. Mixed tocopherols were more potent in preventing platelet aggregation than was alpha-tocopherol alone. Effects of mixed tocopherols were associated with increased NO release, ecNOS activation, and SOD protein content in platelets, which may contribute to the effect on platelet aggregation.